Kondisi Fisik Pemain Persid Jember Berdasarkan Posisi Bermain - Sulaiman, Ahmad; Apriliyanto, Rizki (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2023)
Football attracts the attention of many people because of its level of popularity. Football has spread throughout the world and is played by millions of people from children to adults, including in Indonesia. Football competitions in Indonesia are divided into League 1, League 2 (professional) and League 3 (amateur). Persid Jember is an amateur club member of the PSSI East Java (Jatim) Provincial Association (Asprov) which competes in the 2021 East Java League 3. This research aims to determine the physical condition of Persid Jember players in 2021 based on playing position. Tests and measurements were carried out to collect data on leg muscle power using the Standing Long Jump Test, speed using the 30 meter run, agility using the Illinois Agility Test and aerobic endurance using the Multistage Fitness Test (MFT). Analysis of descriptions with the average of each playing position was carried out in this study. The research results show that there are differences in physical conditions between playing positions, but the most significant is that the goalkeeper position is the lowest among the other positions. This research needs to be developed on larger research subjects considering the limitations of only one club.